2020
DOI: 10.1186/s13287-020-01735-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology in schistosomiasis is regulated by TLR2,4- and IFN-γ-activated MSC through modulating Th1/Th2 responses

Abstract: Background and aims: A marked egg-induced CD4 + T cell programmed inflammation and subsequent hepatic fibrosis characterize the pathogenesis of schistosomiasis. Mesenchymal stem cell (MSC) has been extensively studied for the treatment of schistosomiasis. However, the mechanism by which MSCs modulate the pathogenesis of schistosomiasis has not been clarified. Furthermore, the local inflammatory milieu may greatly influence the immunoregulatory properties of MSCs, and our early experiments demonstrated that Tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The results of the present study suggested that the expression levels of IL-4 and IL-13 in rats with hepatic fibrosis induced by CCl 4 were significantly increased compared with those in normal rats, and the expression of IFN-γ was decreased. This finding is consistent with the results of previous studies, such as in hepatic fibrosis induced by schistosomiasis (11,20). Treatment with TGF-β1 siRNA reduced the degree of hepatic fibrosis, but the expression levels of IL-4 and IL-13 in the liver were not significantly reduced compared with those of the model group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study suggested that the expression levels of IL-4 and IL-13 in rats with hepatic fibrosis induced by CCl 4 were significantly increased compared with those in normal rats, and the expression of IFN-γ was decreased. This finding is consistent with the results of previous studies, such as in hepatic fibrosis induced by schistosomiasis (11,20). Treatment with TGF-β1 siRNA reduced the degree of hepatic fibrosis, but the expression levels of IL-4 and IL-13 in the liver were not significantly reduced compared with those of the model group.…”
Section: Discussionsupporting
confidence: 93%
“…IFN-γ is an important Th1 factor, as it promotes the differentiation of Th1 cells and inhibits the differentiation of Th2 cells (11). IFN-γ can inhibit the activation and proliferation of myofibroblasts and promote their apoptosis, thereby suppressing the production of ECM (12).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding indicated that the anti-AR effect of CGA may be closely related to the inhibition of TH17 differentiation. IFN-γ, a Th1 cell cytokine can suppress Th2 cell proliferation to affect Th1/Th2 balance and induce macrophage production [ 46 , 47 ]. Increased level of IFN-γ contributes to shifting from Th2 to Th1 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TLR family consists of 13 molecules that are widely expressed on immune and non-immune cells in mice. Of these, TLR2/4 is the most important receptor for the recognition of schistosome components ( Zhang et al., 2011 ; Liu et al., 2020 ). However, TLR2 and TLR4 have different effects on schistosome infection.…”
Section: Nlrp3 Inflammasome and Tlr2/4 Signaling Pathwaymentioning
confidence: 99%